According to the sustainability theory, the natural rebalance of resources and wealth may continue in global scenario - Cossiga, Giovanni Antonio (Advances in Social Sciences Research Journal, 2020)
According to the profile of the sustainability economy, the scenario of the nineteenth century, characterized by a colonial structure governed by the major powers, and the imbalance in the wealth distribution that is recorded in today's world are both phenomena dependent on the deviation of the economy from the path of sustainability with nature. Nevertheless, it is inevitable that this deviation will eventually be corrected, and the global economy should then return to the path of a constant and balanced growth. So, leaving the instability world, which today starts from the performance decline and from the general convergence towards price deflation. The fall in the instability world, however, is far from irreversible because we should admit that deflation is a message telling us that things are going wrong, and the economic situation is a tool that is starting the recession to correct the economy in order to bring it back to the balance with the nature. In the sub-world, unfortunately, there are the excesses of an incoherent distribution of resources at a global level, together with the trend towards the concentration of wealth and income within the 10% of families at a local level. A double interlocking that slows down the development potential locally and globally and alters the democracy mechanisms due to the influence that owners of wealth and large incomes undoubtedly can have on the process of selecting the leadership for the economy management. A perverse mechanism that essentially exacerbates the differences in income and resources among peoples and families. In the perspective of the sustainability economy, the movement favoring the concentration cannot continue because the natural correction mechanism comes into play, thus operating according to the times of nature which are quite different from those of our daily lives. Therefore, we can now interpret and understand the amazing work that is globally reshaping the distribution of resources and culture, where Asia is becoming protagonist together with the West of a greater equity and participation. At the moment Africa remains out of this process, though trying to reinforce its pace. The reactions to the so-called globalization are obstacles to the development of process, on which is depending not only the emergence of post-colonial Africa. Because even the development of the global economy is now linked to the continuation of the natural process of rebalancing resources and wealth, not only at a global level but also at the level of states and continents.